Penerapan Reward dan Punishment dalam Pembelajaran Qur’an-Hadits di Sekolah Dasar Kecamatan Muara Tiga Kabupaten Pidie - Maulida, Isna (Master's degree Department of Islamic Education Postgraduate Program of Universitas Islam Negeri (State Islamic University) Ar-Raniry, Banda Aceh in cooperation with Center for Research and Community Service (LP2M), 2019)
A teacher should have a method of learning, so that students are able to learn with fun and has a passion for learning and results. Provide reward and punishment is a way in education to motivate students in the learning process. Focus problem in this research is how the application of reward and punishment in learning the Quran-Hadith in elementary school Muara alam sub-district Pidie district? As for the purpose of this research is to know the application of reward and punishment in learning the Quran-Hadith in elementary school Muara Tiga sub-district Pidie district. As for the place of this research is SDN 1 Curee, SDN 2 Curee, SDN Suka Jaya Kecamatan Muara Tiga. The subject of the study amounted to 6 people: 3 principal and 3 master class. Data collection methods used are observation, interview, and documentation, the instruments used are passing a list of interviews and obeservasi. Technique of data analysis is the reduction of data, display data, and verify the data. As for the results of the research; Application of reward in elementary school Muara Tiga sub-district in the form of gestures, praise, trust, deeds, gifts or even appreciation. As for the punishment in the form of a reprimand, facial appeared irritated, or disregard, clean-up, memorizing the short letter, and Hadith. Positive impact the application of reward and punishment; increase the motivation, the liveliness of students, became the catalyst for the other, students are thrilled. As for the negative impact; the lack of sincere, cause-effect, be apathy. Some of the liveliness of the students after the application of reward and punishment: 1) increase attention to students, 2) increase learning beliefs, 3) increases the satisfaction study, 4) increase the determination of his deeds.